2021
DOI: 10.18371/fcaptp.v1i36.227770
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Investment Security in Ukraine in the Context of Covid-19 and Its Impact on the Financial and Economic Situation of the State

Abstract: Ensuring stable economic development of the country is the main task of state authorities. Investment security is an important component of economic security, plays an important role during the sustainable development of the country’s economy. Modern globalization processes play an important role during the development of the system for the formation and protection of investment security. In addition, the emergence of the COVID-19 pandemic has led to the identification of new negative factors, endogenous and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…These outcomes are consistent with prior research on PIA, including vitality preservation and ecologically accountable shopping (Adetola et al 2021 ). These findings are consistent with earlier research on investment perceptions (Aziz et al 2021 ), for instance, alternative energy implementation, energy competence labeling (Zhang et al 2020 ), and COVID-19 speculation variables (Bobrovska et al 2021 ). In line with the outcomes of previous research, additional research has demonstrated that contribution to PEC proceedings increased investors’ understanding of the significance of vitality proficiency.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These outcomes are consistent with prior research on PIA, including vitality preservation and ecologically accountable shopping (Adetola et al 2021 ). These findings are consistent with earlier research on investment perceptions (Aziz et al 2021 ), for instance, alternative energy implementation, energy competence labeling (Zhang et al 2020 ), and COVID-19 speculation variables (Bobrovska et al 2021 ). In line with the outcomes of previous research, additional research has demonstrated that contribution to PEC proceedings increased investors’ understanding of the significance of vitality proficiency.…”
Section: Discussionsupporting
confidence: 91%
“…These items were embraced and amended based on the previous study (Rana et al 2022 ). As a moderating variable, the role of the Covid-19 financial dynamic was examined by eight items extracted and modified from the research (Bobrovska et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The indicators for assessing the components of economic security of the regions and their limiting values are presented by the authors in Tables 2 and 3. The limit values for the indicators in Table 3 are indicated according to the results of the studies and previous recommendations of the scientists (Sukhorukov, Kharazishvili 2012, Kalina, Savelyeva 2014, Karpov et al 2016, Novikova, Krasnikov 2010, Illarionov 1998 Investment security is a state of the investments being protected from internal and external threats, which allows preventing a decrease in their volume in conditions of an acceptable level of risk (Bobrovska et al 2021). The share of capital investments in Gross Regional Product (GRP) is used to assess investment security.…”
Section: Methodsmentioning
confidence: 99%
“…Third, it saves time and money for the business. [29] The parties to the mediation do not need to spend money on legal costs (which can be significant amounts), the involvement of specialists (for carrying out expert examinations, the cost of which in some cases may be more than the amount of the claim), payment for the services of lawyers [2,[6][7][8]. The expenses of the parties to the mediation are limited to the payment of the mediator's remuneration, the amount of which is determined by agreement between the parties and the mediator and is fixed in the agreement on the use of mediation.…”
Section: Literature Reviewmentioning
confidence: 99%